THE TERM OF "LIFESTYLE" AS THE PEDAGOGICAL PHENOMENON - Kolesnik, Irina A. (Educological discourse, 2014)
The approaches to the definition of "lifestyle" and performed his relationship with such categories as "school climate", "educational space", "lifestyle". Theoretically substantiated the concept of "lifestyle" as a permanent form of everyday life of the educational institution. Justified constituents 'way of life': value, subject-indirect, structural protsesualny. Determined that the conditions of formation of effective ways of life are the traditions of school life and the organizational structure of the institution. The way of life is viewed as a multifaceted phenomenon of life and as a pedagogical category. Based on context analysis identified the essential features lifestyle. The paper analyzes the current research that has allowed to allocate lifestyle elements that need to generate and store in a modern society. The paper presents the way of forming elements lifestyle and introducing them into modern life, and also identified factors that negatively affect its effective establishment.